Urinary Tract Infections by Enterococcus Species: A Retrospective Study at a Tertiary Care Hospital in Dhaka city of Bangladesh (Bangladesh Journal of Medical Microbiology, 2026)
Background: Enterococcus species (Enterococcus species) have progressively transitioned from being commensals to causing severe, life-threatening hospital-acquired infections worldwide, largely due to their natural antimicrobial resistance and virulence potential.Objective: This retrospective study was carried out to determine the prevalence of Enterococcal infections in urine and assess their antibiotic susceptibility patterns at a tertiary care hospital in Dhaka, Bangladesh.Methodology: This six-month retrospective analysis was performed in the Microbiology Laboratory of Dhaka Medical College, Dhaka, Bangladesh. Urine specimens were processed to isolate Enterococcus species using culture methods, microscopic evaluation, and a series of biochemical assays. The antimicrobial resistance patterns of the isolates were examined using the Modified Kirby-Bauer disk diffusion technique. Results: Out of 5,957 urine samples, 872 (14.64%) yielded positive cultures. Among the culture-positive isolates, Gram-positive cocci accounted for 60(6.9%) of the isolates with 52(6.0%) identified as Enterococcus species. In this study, Enterococcus species showed high resistance to ciprofloxacin (82.7%), and doxycycline (65.4%). However, they were highly susceptible to linezolid (100.0%), vancomycin (94.2%), and teicoplanin (92.3%).Conclusion: Our study highlights a significant prevalence of resistance to ciprofloxacin, and doxycycline among Enterococcal isolates in urine. The prevalence of vancomycin-resistant Enterococci (VRE) continues to rise. Vancomycin and teicoplanin, both glycopeptide antibiotics, exhibit similar resistance rates, making teicoplanin a viable alternative to vancomycin.Bangladesh Journal of Medical Microbiology, July 2025;19 (2):95-99